Bilateral anterior ischaemic optic neuropathy associated with optic disc drusen and systemic hypotension. Issue 9 (September 1989) - Michaelson, C; Behrens, M; Odel, J
Abstract : We report a case of bilateral anterior ischaemic optic neuropathy in a 23-year-old woman which was probably attributable to optic disc drusen and systemic hypotension related to peritoneal dialysis for renal failure.